2021
DOI: 10.1111/ddi.13278
|View full text |Cite
|
Sign up to set email alerts
|

Fire and functional traits: Using functional groups of birds and plants to guide management in a fire‐prone, heathy woodland ecosystem

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
0
8
1
2
Order By: Relevance
“…This result contrasts markedly with other studies elsewhere in Australia and globally that have found life history trait-mediated responses to disturbances (Gerisch et al, 2012;Haddad et al, 2008;Hansen & Urban, 1992;Hidasi-Neto et al, 2012;Ikin et al, 2019), including wildfire (e.g. Rainsford et al, 2021). For example, Rainsford et al (2021) uncovered evidence of associations between fire, vegetation structure, and the foraging strategy and nesting type of birds in fire-prone heathland in western Victoria.…”
Section: Q2 Do Bird Life History Attributes Explain Recovery Trajecto...contrasting
confidence: 97%
“…This result contrasts markedly with other studies elsewhere in Australia and globally that have found life history trait-mediated responses to disturbances (Gerisch et al, 2012;Haddad et al, 2008;Hansen & Urban, 1992;Hidasi-Neto et al, 2012;Ikin et al, 2019), including wildfire (e.g. Rainsford et al, 2021). For example, Rainsford et al (2021) uncovered evidence of associations between fire, vegetation structure, and the foraging strategy and nesting type of birds in fire-prone heathland in western Victoria.…”
Section: Q2 Do Bird Life History Attributes Explain Recovery Trajecto...contrasting
confidence: 97%
“…Additionally, many of the restoration methods applied in less degraded starting conditions (e.g. burning, thinning, mowing) could select for specific suites of species adapted to these treatments (Pausas & Bradstock, 2007; Rainsford et al, 2021; Shryock et al, 2014), as well as being broadly more homogenous treatments compared with those employed in complex interventions, resulting in less variable outcomes. These particular low‐degradation methods may also provide more suitable environmental conditions for species found in reference ecosystems and, therefore, result in more consistently successful restoration.…”
Section: Introductionmentioning
confidence: 99%
“…A landscape composed of a mosaic of patches at different time periods since burning is more pyro-biodiverse than a single large space caused by a megafire. Similarly, in a landscape mosaic composed of forest patches with different resilience to fire [16,17], the occurrence of a large fire can enhance biodiversity by the combination of species adapted to unburnt and burnt habitats [18].…”
Section: Introductionmentioning
confidence: 99%